Generation of hypoimmunogenic human pluripotent stem cells via expression of membrane‐bound and secreted β2m‐HLA‐G fusion proteins. (15th September 2020) - Shi, Lei; Li, Wenjing; Liu, Yang; Chen, Zhenyu; Hui, Yi; Hao, Pengcheng; Xu, Xiangjie; Zhang, Shuwei; Feng, Hexi; Zhang, Bowen; Zhou, Shanshan; Li, Nan; et al.
Abstract: Allogeneic immune rejection is a major barrier for the application of human pluripotent stem cells (hPSCs) in regenerative medicine. A broad spectrum of immune cells, including T cells, natural killer (NK) cells, and antigen‐presenting cells, which either cause direct cell killing or constitute an immunogenic environment, are involved in allograft immune rejection. A strategy to protect donor cells from cytotoxicity while decreasing the secretion of inflammatory cytokines of lymphocytes is still lacking. Here, we engineered hPSCs with no surface expression of classical human leukocyte antigen (HLA) class I proteins via beta‐2 microglobulin ( B2M) knockout or biallelic knockin of HLA‐G1 within the frame of endogenous B2M loci. Elimination of the surface expression of HLA class I proteins protected the engineered hPSCs from cytotoxicity mediated by T cells. However, this lack of surface expression also resulted in missing‐self response and NK cell activation, which were largely compromised by expression of β2m‐HLA‐G1 fusion proteins. We also proved that the engineered β2m‐HLA‐G5 fusion proteins were soluble, secretable, and capable of safeguarding low immunogenic environments by lowering inflammatory cytokines secretion in allografts. Our current study reveals a novel strategy that may offer unique advantages to construct hypoimmunogenic hPSCs via the expression of membrane‐bound and secreted β2m‐HLA‐G fusion proteins. These engineered hPSCs are expected to serve as an unlimited cell source for generating universally compatible "off‐the‐shelf" cell grafts in the future. Abstract : Novel hypoimmunogenic human pluripotent stem cells (hPSCs) are constructed by targeting beta‐2 microglobulin and HLA‐G proteins. The engineered hypoimmunogenic hPSCs are compatible with T cell‐ and natural killer cell‐mediated immunotoxicity and are capable of safeguarding low immunogenic environments in allografts. These hypoimmunogenic hPSCs can serve as invaluable cell sources for a regenerative purpose.